INFLUENCE OF MINERAL FILLERS ON PHYSICAL AND MECHANICAL PROPERTIES OF GYPSUM CONCRETE COMPOSITIONS - Prof. A. I. Xamidov; Dots. M. A. Mirzajanov; Doctoral Sh.Sh.Kuziboev (Journals Park Publishing, 2022)
The article describes the physical and mechanical characteristics of gypsum concrete compositions modified with pulverized marble and travertine waste. It is shown that the increase in the physical and mechanical properties of composite materials is primarily due to the formation of new phases with the chemical participation of soluble marble and travertine minerals in the heterogeneous process of gypsum hardening, as well as the formation of gypsum stone. In a more perfect structure, both marble and travertine particles fill the pore space of the binder.
Keywords: marble, travertine, filler, gypsum concrete, waste, particle size distribution, particles